Black Phosphorus Rediscovered: From Bulk Material to Monolayers - Gusmão, Rui; Sofer, Zdenek; Pumera, Martin (Angewandte Chemie (International ed. in English), 2017)
Phosphorus is a nonmetal with several allotropes, from the highly reactive white phosphorus to the thermodynamically stable black phosphorus (BP) with a puckered orthorhombic layered structure. The bulk form of BP was first synthesized in 1914, but received little attention until it was rediscovered in 2014 as a member of the new wave of 2D layered nanomaterials. BP can be exfoliated to a single sheet that acts as a semiconductor with a tunable direct band gap, a high carrier mobility at room temperature, and an in-plane anisotropy. The development of BP applications is hampered by surface degradation, thus efforts to achieve effective BP passivation are ongoing, such as its integration in van der Waals heterostructures. BP has been tested as a novel nanomaterial in batteries, transistors, sensors, and photonics. This Review begins with the origin of the BP story, following the path from a bulk material to modern few/single layers. The physical and chemical properties are summarized, and the state-of-the-art of BP applications highlighted.
Keywords: black phosphorus; anisotropy; 2D nanomaterials; phosphorene